In vivo wide‐field voltage imaging in zebrafish with voltage‐sensitive dye and genetically encoded voltage indicator. (18th October 2021) - Hiyoshi, Kanae; Shiraishi, Asuka; Fukuda, Narumi; Tsuda, Sachiko
Abstract: The brain consists of neural circuits, which are assemblies of various neuron types. For understanding how the brain works, it is essential to identify the functions of each type of neuron and neuronal circuits. Recent advances in our understanding of brain function and its development have been achieved using light to detect neuronal activity. Optical measurement of membrane potentials through voltage imaging is a desirable approach, enabling fast, direct, and simultaneous detection of membrane potentials in a population of neurons. Its high speed and directness can help detect synaptic and action potentials and hyperpolarization, which encode critical information for brain function. Here, we describe in vivo voltage imaging procedures that we have recently established using zebrafish, a powerful animal model in developmental biology and neuroscience. By applying two types of voltage sensors, voltage‐sensitive dyes (VSDs, Di‐4‐ANEPPS) and genetically encoded voltage indicators (GEVIs, ASAP1), spatiotemporal dynamics of voltage signals can be detected in the whole cerebellum and spinal cord in awake fish at single‐cell and neuronal population levels. Combining this method with other approaches, such as optogenetics, behavioral analysis, and electrophysiology would facilitate a deeper understanding of the network dynamics of the brain circuitry and its development. Abstract : We describe the procedure of in vivo voltage imaging in the zebrafish cerebellum and spinal cord with voltage‐sensitive dyes and genetically encoded voltage indicators. Wide‐field fluorescence microscopy allows spatiotemporal analysis of voltage signals at single‐cell and neuronal population levels in vivo.